Contribution to Society: A Footnote for the Care Act 2014. Issue 5 (19th October 2016) - Diaper, Andy; Yeomans, Paul
Abstract : Between 1 April 2015 and 1 April 2016 local authorities in England have to introduce a new system of needs assessment, carer's assessment and care and support planning for adult social care. The new legislation changes the eligibility criteria and with it a definition of 'well-being' that must be considered in all adult care-related activity. Part of this definition is the individual's contribution to society. There is no explanation of what this term means, and so ahead of relevant case law by the courts, this article discusses interpretations which may help practitioners discharge their legal duties and abide by professional standards.